سياسة استهداف التضخم: المُتطلبات وتجارب التطبيق - هناء عبدالكريم خليفة (Scientific Journal of University of Benghazi, 2020)
This paper aims to shed light on the policy of targeting inflation. As amodern monetary policy was applied for the first time in 1990, where it was adopted by many developed countries and emerging markets, with focusing on the most important requirements of the adoption of this policy and its advantages, in addition to the experiences of some countries applying it. This paper found that this policy despite its modernity, succeeded in the countries that have applied it, where inflation rates have fallen, and in return achieved good economic growtg rates.It also concluded that to judge on the effectiveness of the targeting inflation policy in any country is related to the availability of the conditions of applying the policy in that country.